(untitled) (Palíndromo, 2018)
This paper aims to think possible interweaving between politics, body and city, inside the poetics of the Opavivará! ensemble, based in the city of Rio de Janeiro. Firstly we present some relations between the powers that conforms the urban space and the production of subjectivities, explaining how contemporary urban experience hinders processes of singularization. Then we point out how ensembles can be important political subjects contemporarly. At the end we analyze some of the mentioned above ensemble’s pieces.